Value of Contrast-Enhanced Ultrasound for Evaluation of Cervical Lymph Node Metastasis in Papillary Thyroid Carcinoma - Fang, Fengkai; Gong, Yi; Liao, Liyan; Ye, Fei; Zuo, Zhongkun; Li, Xiaodu; Zhang, Qi; Tang, Kui; Xu, Yan; Zhang, Rongsen; Chen, Sijie; Niu, Chengcheng (Frontiers in Endocrinology, 2022)
The aim of the study was to evaluate the diagnostic value of contrast-enhanced ultrasound (CEUS) in distinguishing between benign and malignant cervical lymph nodes (LNs) in patients with papillary thyroid carcinoma (PTC). Two hundred and one cervical LNs (157 metastatic from PTC and 44 benign) were evaluated using conventional ultrasonography (US) and CEUS before biopsy or surgery. Histopathology was used as the gold standard. We evaluated the size, long axis/short axis ratio (L/S), fatty hilum, hyper-echogenicity, calcification, cystic change, peripheral vascularity and CEUS parameters for each lymph nodule. The CEUS parameters included enhancement type, homogeneity, perfusion type, ring enhancement, peak intensity (PI) index and area under the curve (AUC) index. Univariate analysis demonstrated that compared with benign LNs, malignant LNs more frequently had L/S < 2, absence of a fatty hilum, presence of hyper-echogenicity, presence of calcification, peripheral vascularity, hyper-enhancement, heterogeneous enhancement, centripetal perfusion, ring enhancement, PI index ˃ 1 and AUC index ˃ 1 on preoperative US and CEUS. Binary logistic regression analysis demonstrated that hyper-enhancement, centripetal perfusion, and ring enhancement are independent CEUS characteristics related to malignant LNs for their differentiation from benign LNs (all p < 0.05). Our study indicated that preoperative CEUS characteristics may serve as a useful tool to identify malignant cervical LNs from benign cervical LNs.